2004
DOI: 10.1161/01.atv.0000116027.81513.68
|View full text |Cite
|
Sign up to set email alerts
|

C-Peptide Colocalizes with Macrophages in Early Arteriosclerotic Lesions of Diabetic Subjects and Induces Monocyte Chemotaxis In Vitro

Abstract: Objective-Increased levels of C-peptide, a cleavage product of proinsulin, circulate in patients with insulin resistance and early type 2 diabetes, a high-risk population for the development of a diffuse and extensive pattern of arteriosclerosis. This study tested the hypothesis that C-peptide might participate in atherogenesis in these patients. Method and Results-We demonstrate significantly higher intimal C-peptide deposition in thoracic artery specimens from young diabetic subjects compared with matched no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 25 publications
4
103
1
2
Order By: Relevance
“…In vitro cell migration assay The migration of isolated monocytes was determined as previously described [20]. Briefly, cells were cultured in serum-free media for 16 h. Monocytes (5×10 6 cells/ml) were pretreated for 30 min with GLP-1(7-36) (Sigma) at the concentrations indicated in serum-free medium and subsequently assayed for chemotaxis under serum-free conditions in a 48-well microchemotaxis chamber (Neuroprobe, Leamington Spa, Warwickshire, UK).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro cell migration assay The migration of isolated monocytes was determined as previously described [20]. Briefly, cells were cultured in serum-free media for 16 h. Monocytes (5×10 6 cells/ml) were pretreated for 30 min with GLP-1(7-36) (Sigma) at the concentrations indicated in serum-free medium and subsequently assayed for chemotaxis under serum-free conditions in a 48-well microchemotaxis chamber (Neuroprobe, Leamington Spa, Warwickshire, UK).…”
Section: Methodsmentioning
confidence: 99%
“…C peptide has been shown to be expressed in atherosclerotic lesions from diabetic patients [61]. In vitro, C-peptide displayed chemotactic activity towards monocytes via a Gprotein coupled receptor and phosphatidylinositol-3 kinase-(PI3K)-dependent mechanism [61] and induced proliferation of vascular smooth muscle cells [62].…”
Section: Peptidementioning
confidence: 99%
“…4,5 C-peptide deposition occurs in the atherosclerotic lesions of patients with diabetes. 6 Recent studies have suggested that Cpeptide may be a valuable predictor of cardiovascular events and mortality (all-cause and cardiovascular-related mortality). [6][7][8][9][10][11][12] In this study, we investigated the association between serum C-peptide level and all-cause, cardiovascular-related and coronary artery disease-related mortality among patients without diabetes.…”
mentioning
confidence: 99%